Analisis Permainan Bahasa dalam Ungkapan “Wacana Penundaan Pemilu Tahun 2024”: Perspektif Ludwig Wittgenstein - Mohammad Fajar Setiawan; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
The discourse of postponing the 2024 election has generated many responses from various groups. In these expressions, of course, using language and the language used in these expressions can cause various responses. Therefore, this study aims to dissect the language context in the expression